(untitled) (Bangladesh Journal of Public Administration, 2022)
Encouraging participation through local governments has been questionable and democratic spirit with direct participation of common people has always been poorly valued. The Union Parishads, in spite of having constitutional provision, could not come out as self governing units and left under the command of national government. The objectives of this study was to assess how participation makes LGSP effective in improving ICT literacy in rural areas of Bangladesh and to identify how LGSP plays pivotal role to build capacity of students and unemployed people of the study area. Both qualitative and quantitative methods and standardized statistical application SPSS were used in the study. The study was based on empirical data from eight (08) Unions of Kishoreganj Upazila of Nilphamari District. The study reveals that the projects under LGSP are usually taken after consultation with the rural people through Ward Meeting .However, the number of ICT related projects were very low ; only 2 to 3 projects were taken by each of the union council in a fiscal year. Most of the projects under LGSP were on construction of road and culverts, installing tube-well, developing rural drainage and renovation of sewerage system because the elected representatives are interested on such types of small projects. On the other hand, the role of LGSP in building capacity of the unemployed youths and students was found to be very noteworthy as they received different digital services and skill oriented training ranging from online job application, photocopying, printing, registration and other e- services ; creating a new job opportunities and self run businesses. Therefore, this study recommended to take more ICT and other skill oriented projects and to increase budget for advanced level ICT training for rural youths; which may contribute to developing freelancing and entrepreneurship amongst them .This study will create value to the research arena and the implementing agencies will think out of the box while giving effort on capacity development through LGSP.